Juridical Analysis Of The Comparison Of Election Costs In Indonesia And The United States In Legislative Elections - Nasarudin, Tubagus Muhammad; Aulia, Salita; Wibowo, Prasetio Agung (Universitas Malayati, 2024)
General elections according to the Big Indonesian Dictionary (KBBI) are elections carried out simultaneously by all the people of a country to elect people's representatives and so on. The research methodology in this writing uses a normative approach. The research results show that in the Indonesian and American elections there are several differences, such as the type of institution authorized to organize elections and the procedures for conducting elections. However, the Indonesian and American elections also have several similarities, especially in the economic field. On the economic side, holding elections affects the dynamics of the national economy. Political activities will increase public consumption, from preparation to implementation of elections, including government spending on organizing elections to campaign spending.Keywords: Election, Indonesia, America